A survey on collections of audiovisual materials in selected media centers in Quezon City - Quinto, Mae Lyn P. (2008)
The study attempted to study the audiovisual materials administration of Media Centers in selected private high schools in Quezon City. Specifically, it aimed to identify the audiovisual materials and equipment available in the Media Centers, the selection and acquisition, cataloging and classification and utilization of audiovisual materials, audiovisual materials used by the teachers as instructional tools, assessment by teachers of the existing audiovisual collection and its services; and lastly, determine the collaboration of media specialists and teachers in terms of growth and utilization of the audiovisual materials.